Submonolayer biolasers for ultrasensitive biomarker detection - Gong, Chaoyang (2024)
Biomarker detection is key to identifying health risks. However, designing sensitive and single-use biosensors for early diagnosis remains a major challenge. Here, we report submonolayer lasers on optical fibers as ultrasensitive and disposable biosensors. Telecom optical fibers serve as distributed optical microcavities with high Q-factor, great repeatability, and ultralow cost, which enables whispering-gallery laser emission to detect biomarkers. It is found that the sensing performance strongly depends on the number of gain molecules. The submonolayer lasers obtained a six-order-of-magnitude improvement in the lower limit of detection (LOD) when compared to saturated monolayer lasers. We further achieve an ultrasensitive immunoassay for a Parkinson's disease biomarker, alpha-synuclein (α-syn), with a lower LOD of 0.32 pM in serum, which is three orders of magnitude lower than the α-syn concentration in the serum of Parkinson's disease patients. Our demonstration of submonolayer biolaser offers great potentials in high-throughput clinical diagnosis with ultimate sensitivity.